Observational clinical study on the effects of different dosing regimens on vancomycin target levels in critically ill patients: Continuous versus intermittent application. Issue 4 (July 2015) - Tafelski, S.; Nachtigall, I.; Troeger, Uwe; Deja, Maria; Krannich, Alexander; Günzel, Karsten; Spies, C.; for the ABx Study Group
Summary Different dosing regimens for vancomycin are in clinical use: intermittent infusion and continuous administration. The intention of using these different dosing regimens is to reduce toxicity, to achieve target levels faster and to avoid treatment failure. The aim of this phase IV study was to compare safety and effectiveness in both administration regimens. The study was conducted in 2010 and 2011 in three postoperative intensive care units (ICUs) in a tertiary care university hospital in Berlin, Germany. Adult patients with vancomycin therapy and therapeutic drug monitoring were included. Out of 675 patients screened, 125 received vancomycin therapy, 39% with intermittent and 61% with continuous administration. Patients with continuous administration achieved target serum levels significantly earlier (median day 3 versus 4, p = 0.022) and showed fewer sub-therapeutic serum levels (41% versus 11%, p < 0.001). ICU mortality rate, duration of ICU stay and duration of ventilation did not differ between groups. Acute renal failure during the ICU stay occurred in 35% of patients with intermittent infusion versus 26% of patients with continuous application (p = 0.324). In conclusion, continuous administration of vancomycin allowed more rapid achievement of targeted drug levels with fewer sub-therapeutic vancomycin levels observed. This might indicate that patients with more severe infections or higher variability in renal function could benefit from this form of administration.